THE STEREOTYPE OF AFRO-AMERICAN FATHER IN FATHERHOOD (2021) MOVIE: COUNTER DISCOURSE - Julqaidah, Julqaidah; Nasrum, Nasrum; Junaid, Syahruni (Journal of Islamic Culture and Literature (JICeL), 2025)
This research explains about stereotypes of father roles in the movie “Fatherhood” by Paul Weitz using Charles Stangor's stereotype theory (2021) and Cohen and Garcia's stereotype denial theory (2005). It aims to identify father stereotypes in the Fatherhood movie. In society and the media, there have been stereotypes about Afro-American fathers. Studies reveal that Afro-American fathers are often absent in their children's lives. The researchers used descriptive qualitative method and stereotype theory, assisted by movie narrative in analyzing the data. Primary data are images, narratives, and dialog in the movie Fatherhood (2021). This research found seven issues that are considered as a counter-discourse to the stereotype of Afro-American fathers. They are responsible, attentive, financially concerned, health concerned, educating and encouraging to the Afro-American father figure. The paternal bound also exists in the figure. Keywords: Afro-American, movie, stereotype, stereotype denial.